Aesthetic experience : beauty, creativity, and the search for the ideal - Hagman, George (Contemporary psychoanalytic studies ;, 2005)
"George Hagman looks anew at psychoanalytic ideas about art and beauty through the lens of current developmental psychology that recognizes the importance of attachment and affiliative motivational systems. In dialogue with theorists such as Freud, Ehrenzweig, Kris, Rank, Winnicott, Kohut, and many others, Hagman brings the psychoanalytic understanding of aesthetic experience into the 21st century. He amends and extends old concepts and offers a wealth of stimulating new ideas regarding the creative process, the ideal, beauty, ugliness, and -perhaps his most original contribution-the sublime.